Performance of confined concrete columns under simulated life cycles - Hart, Steven D. (Kansas State University, 2008)
Over the past 30 years, FRP composites (carbon, glass, or aramid fibers) have arisen as a method of retrofitting existing reinforced concrete structures to bring them up to current code standards of confinement and ductility. The development of stress-strain models for FRP confined concrete began with the adaptation of steel confinement models then progressed to models specifically developed based on test results from FRP confined specimens. State of the art stress-strain models for FRP confined concrete models may now be validated against a wide variety of published experimental results. Recent publications show researchers branching out and looking at other aspects of FRP confined concrete behavior, including the impact of sustained service loads on long term and ultimate behavior. An experimental program which examines the effects of sustained service loading on the ultimate axial performance of FRP confined concrete is presented. The program's purpose is to determine whether or not a material model developed without the presence of a sustained load accurately predicts the ultimate stress-strain response of FRP confined concrete previously subjected to a sustained service load. Equipment and procedures were developed to model the critical events in a building life cycle: construction, sustained service loading, minor critical events, rehabilitation, and ultimate performance. Varying the order of these events produces a simulated life cycle allowing analysis of the impact of strain history on ultimate performance. The results of the experimental program indicate that the presence of a sustained service load changes the expected failure mode from FRP rupture to FRP de-lamination and the stress-strain response of a specimen is approximately 10% below published models when sustained service loads are included in the life cycle. A comprehensive modeling process is proposed for modeling significant events in a structure's life cycle. Impacts on earthquake engineering and reliability studies are addressed and future research suggested. This research shows that life cycle modeling can improve the design and rehabilitation of structures so that they meet safety requirements in future seismic events.
Keywords: Confined Concrete; Fiber reinforced polymer; Sustained load; Stress-strain model; Engineering, Civil (0543)